2018
DOI: 10.1080/13696998.2018.1427100
|View full text |Cite
|
Sign up to set email alerts
|

Societal costs of multiple sclerosis in Ireland

Abstract: The findings highlight that up to 70% of the total costs associated with MS are not routinely counted. These "hidden" costs are higher in Ireland than the rest of Europe, due in part to significantly lower levels of workforce participation, a higher likelihood of permanent workforce withdrawal, and higher levels of informal care needs. The relationship between disease progression and costs emphasize the societal importance of managing and slowing the progression of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…The health utility ranged from 0.31 to 0.78 for multiple sclerosis patients in six studies (34)(35)(36)(37)(38)(39). The upper and lower utility values were generated with the crosswalk France value set (35) and the crosswalk UK value set (39), respectively.…”
Section: Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…The health utility ranged from 0.31 to 0.78 for multiple sclerosis patients in six studies (34)(35)(36)(37)(38)(39). The upper and lower utility values were generated with the crosswalk France value set (35) and the crosswalk UK value set (39), respectively.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…In addition, the former had a higher proportion of relapsingremitting multiple sclerosis patients than the latter (71.5 vs. 52.8%). EQ-5D VAS scores ranged from 58.3 to 78.0 in five studies (35)(36)(37)(38)(39). Pain/discomfort and usual activities were the dimensions with the most reported problems among multiple sclerosis patients.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…2829 A population based cohort study found that people with MS have a threefold higher risk of hip fracture than age and gender matched peers with a greater risk for those prescribed steroids in the previous six months. 30 Injurious falls can result in increased healthcare utilisation and decreased labour force productivity which both contribute to the high socio-economic cost associated with MS 31,32 .…”
Section: Consequences Of Fallsmentioning
confidence: 99%
“…However, this protective response may result in some people with MS curtailing their activities inappropriately, resulting in further deconditioning and adversely affecting physical function and independence s. 40 This adverse response should be avoided especially due to the growing body of evidence highlighting the benefits of regular physical activity for MS. 41 Most concerning is that studies have consistently found that fallers have lower quality of life than non-fallers 14,42 Lower quality of life, in turn, has higher associated socio-economic costs, and contributes significantly to the intangible costs and burden for the person with MS related to issues around self-care, pain, anxiety and depression. 32 Nilsagard et al 43 qualitatively explored the context and impact of accidental falls in pwMS, with participants describing falls as limiting, restrictive and embarrassing.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…The social costs of MS are higher than those associated with strokes or Alzheimer's disease. It is associated with onset in early to middle adulthood, duration of the disease (It has a relatively small impact on life expectancy, so there is a need to treat the patient for many years), early loss of work capacity due to disability, wide range of symptoms, the need for care and assistance in carrying out daily activities, and the high cost of immunomodulatory therapies or interdisciplinary medical care [4,5]. Due to the increase of disability and the impact of the disease on daily functioning, most patients need social support from their environment.…”
Section: Introductionmentioning
confidence: 99%